An Analysis of Body Language of Grade 8Th Students in English Lesson at SMP Negeri 9 Kupang - Mariana Elisabet Mau Muskanan; Sebastianus Fernandez; Reyneldis Fernandez (Universitas Nusa Cendana, 2025)
The purpose of this study is to assist teachers, especially English teachers, in understanding the body language used by students during the teaching and learning process as a means of communication to indicate their interest in the lesson. This research employs a descriptive qualitative method. The subjects of the study are the students of Class VIII D at SMP Negeri 9 Kupang. The data collection instruments include observation tables, a camera for photos and videos, and writing tools such as notebooks and pens. Based on the findings, there are 16 types of body language produced during the learning process, namely: resting chin on hand, staring out the window, nodding, actively taking notes, occasionally covering the face with hands, apathetic facial expressions, playing with objects on the desk, making eye contact, sitting or standing lazily, using the phone without teacher instructions, forced smile or blank expression, yawning, slouching in the seat, doodling in the notebook, positive facial expressions, and briefly discussing with a classmate. There are also four categories of body language identified during the learning process: (1) eye contact, for example, looking directly at the teacher indicates attention; (2) facial expressions, such as forced smiles and positive expressions like smiling indicate boredom or amusement; (3) gestures, such as nodding which signifies agreement or understanding; and (4) body posture, for example, leaning forward while sitting or standing upright shows confidence or readiness.